2022
DOI: 10.1063/5.0082945
|View full text |Cite
|
Sign up to set email alerts
|

The phase effect on the Richtmyer–Meshkov instability of a fluid layer

Abstract: Shock-induced finite-thickness fluid layer evolution is investigated numerically and theoretically. Specifically, two-dimensional helium layers consisting of two interfaces owning diverse perturbation phases are considered to explore the interface-coupling on the Richtmyer–Meshkov instability (RMI). A general linear model is first established to quantify the phase effect on the RMI of the two interfaces of an arbitrary fluid layer. The linear model is validated with the present numerical results. As the phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…2019; Liang et al. 2020 b ; Liang 2022 b ). A comprehensive review of the scheme and its extensive applications was recently reported by Jiang, Wen & Zhang (2020).…”
Section: Experimental and Numerical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2019; Liang et al. 2020 b ; Liang 2022 b ). A comprehensive review of the scheme and its extensive applications was recently reported by Jiang, Wen & Zhang (2020).…”
Section: Experimental and Numerical Methodsmentioning
confidence: 99%
“…Open boundary conditions are enforced on the left and right boundaries ( and mm) to eliminate the waves reflected from the left and right boundaries (Liang et al. 2020 b ; Liang 2022 b ), and reflection conditions are imposed at the top and bottom boundaries ( and mm), respectively.
Figure 2.Schematics of the initial simulation setup, where and represent the amplitudes of the upstream interface and downstream interface, respectively.
…”
Section: Experimental and Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the research progresses, the problem being studied and the models being used are becoming more and more practical and complex [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In recent years, the results in statistical physics perspectives obtained with the help of Discrete Boltzmann Method (DBM) and complex physical field analysis techniques have also provided a range of new insights into the study of hydrodynamic instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…RMI has also been extensively studied [34][35][36][37] in theory [38][39][40][41][42] , numerical simulations [43][44][45][46][47][48][49][50][51][52][53][54][55][56] , and experiments [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] for general conditions. The physical comprehension of RMI is becoming clearer, however, as for general fluid cases, there are also significant nonequilibrium kinetic effects and this part is missing for the majority of existing studies.…”
Section: Introductionmentioning
confidence: 99%